PERAN EDUKASI CORPORATE SOSIAL RESPONSIBILITY DALAM MENINGKATKAN KESADARAN GREEN ECONOMIC DI KALANGAN SISWA SMA NEGERI 16 KABUPATEN TANGERANG - Elinda (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2025)
Environmental education has become increasingly important to raise awareness and understanding among the younger generation about the importance of protecting, preserving, and maintaining the environment. One effort that can be done is through education on Corporate Social Responsibility (CSR) and the concept of a green economy among students as the future generation. The problem faced is the lack of knowledge among students at SMA Negeri 16 Kabupaten Tangerang regarding the implementation of a green economy through Corporate Social Responsibility (CSR) education, and there are still many students who need awareness of the importance of a green economy and Corporate Social Responsibility (CSR) as provisions for their future. This community service aims to increase students' understanding and awareness of implementing a green economy through Corporate Social Responsibility (CSR) education and instill the importance of a green economy as a provision for their future. The method used is a 2-hour educational seminar on green economics and Corporate Social Responsibility (CSR), and posters containing information about the green economy and CSR have also been made by the committee to be given to the school so that they can be understood and applied in daily life and provide benefits for all students. The evaluation results show that most participants felt the activity was beneficial, the material was well-presented, and the presentation method was interesting. It can be concluded that this activity has succeeded in increasing students' knowledge and awareness. It is recommended to carry out follow-up activities, expand collaboration with schools and other relevant parties, and utilize digital media to disseminate information on an ongoing basis.